2020
DOI: 10.1177/1559325820941323
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Fabrication of Dose–Response Chitosan/Dextran/β-Glycerophosphate Injectable Hydrogel as Cell Delivery Carrier for Cardiac Healing After Acute Myocardial Infarction

Abstract: The human mesenchymal stem cells (hMSCs) therapy offering an encouraging the new methods to establish the conveying on the chitosan (C)/dextran (D)/β-glycerophosphate (β-GP) loaded with hMSCs to enhance the acute myocardial infarctions. The synthesized hMSCs-CD@β-GP system displayed the ratio of determination modules, size of the pore, absorbency, and the swellings ratio in the assortment of the 65 ka, 149 ± 39.8 µm, 92.2%, 42 ± 1.38, and 29 ± 1.9, respectively. The fabricated hMSCs-CD@β-GP was highly stable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…These materials have good biocompatibility and could promote nutrient exchange and metabolic substance discharge for stem cells, which is conducive to cell viability. 135,136 Meanwhile, the suitable pore sizes may display a sustained-release profile. Chiang et al 33 developed a temperature-sensitive hydrogel containing hepatocytelike cells (iPSC-Heps), carboxymethyl-hexanoyl chitosan, and hepatocyte growth factor (HGF-CHC).…”
Section: Thermosensitive Hydrogelmentioning
confidence: 99%
“…These materials have good biocompatibility and could promote nutrient exchange and metabolic substance discharge for stem cells, which is conducive to cell viability. 135,136 Meanwhile, the suitable pore sizes may display a sustained-release profile. Chiang et al 33 developed a temperature-sensitive hydrogel containing hepatocytelike cells (iPSC-Heps), carboxymethyl-hexanoyl chitosan, and hepatocyte growth factor (HGF-CHC).…”
Section: Thermosensitive Hydrogelmentioning
confidence: 99%
“…Studies have shown that the chitosan (CS)/dextran (D)/β-glycerophosphate (β-GP) loaded with human mesenchymal stem cells (hMSCs) enhanced cardiac healing in acute myocardial infarction [ 82 ]. Bioactive chitosan hydrogel has also been shown to be promising in the stem cell regeneration of cardiac function.…”
Section: Stem Cell-based Therapies Utilizing Chitosan For Cardiac Disordersmentioning
confidence: 99%
“…The need for polymeric drug delivery was driven by the nonspecific distribution of drugs, toxicity, and response of the body to the certain drugs. [1][2][3][4] The biodegradable sutures were first obtained by hair, tendons, plant, and wool fibers by Egyptians. The earliest synthesized polymers were used in the 1960s and 1970s.…”
Section: Introductionmentioning
confidence: 99%